Protective effect of Globularia alypum leaves against deltamethrin-induced nephrotoxicity in rats and determination of its bioactive compounds using high-performance liquid chromatography coupled with electrospray ionization tandem quadrupole–time-of-flight mass spectrometry - Feriani, Anouar; del Mar Contreras, María; Talhaoui, Nassima; Gómez-Caravaca, Ana María; Taamalli, Amani; Segura-Carretero, Antonio; Ghazouani, Lakhdar; El Feki, Abdelfatteh; Allagui, Mohamed Salah (Journal of functional foods, 2017)
•RP-HPLC-DAD-ESI-QTOF-MS/MS analysis of Globularia alypum extract was performed.•Thirty-nine compounds were identified and quantified.•Protective effect of G. alypum against deltamethrin induced nephrotoxicity was determined.•G. alypum reduces the DNA damage and fibrosis in the kidney. This study was designed to investigate the protective effects of Globularia alypum leaves extract (GE) against the nephrotoxicity provoked by a chronic exposure to deltamethrin (DLM) in rats. High-performance liquid chromatography coupled with electrospray ionization tandem quadrupole–time-of-flight mass spectrometry (HPLC-DAD-ESI-QTOF-MS) analysis revealed the presence of thirty-nine compounds among them globularin was the major compound (9444mg/100g of dry matter). Results showed that DLM administration altered the renal functions. Whereas, GE treatment restored the increased plasma creatinine, urea and uric acid levels, reduced the elevated MDA and PC levels, significantly normalized the antioxidant enzyme activities. In addition, histopathologic examination confirmed the deltamethrin damage to the renal tissue and revealed renal connective tissue fibrosis and severe necrosis of the proximal tubules with haemorrhage, which was corrected by GE treatment. Therefore, it was speculated that GE presented a protective effects against deltamethrin induced nephrotoxicity through the action of its bioactive compounds.